Indigenous and Traditional Visual Artistic Practices: Implications for Art Therapy Clinical Practice and Research - Kaimal, Girija; Arslanbek, Asli (Frontiers in Psychology, 2020)
In this paper, we present a review of research on the role of traditional and indigenous forms of visual artistic practice in promoting physical health and psychosocial well-being, particularly as it relates to the discipline of art therapy. Using extant literature we present an overview of how art making has historically had a therapeutic role in human lives and how it can inform the modern interpretation and profession of art therapy. Thereafter, we provide a critical review of specific studies that reference traditional and indigenous art forms in art therapy in order to invite discussion, dialogue, and awareness of the role of the arts in human development and the therapeutic role of the arts. Gaps in research areas for further study are proposed. Implications for clinical practice including expanding the scope of traditional forms of creative self-expression and promoting an informed and respectful understanding of the role of these artforms in the profession of art therapy worldwide, are also discussed.